HUBUNGAN PERILAKU MEROKOK DAN KONSUMSI MAKANAN BERLEMAK DENGAN KEJADIAN PENYAKIT JANTUNG PADA LANSIA DI INDONESIA (ANALISIS RISKESDAS 2018) - Nada Sausan Salsabilla Amri Reeng (2023)
Cardiovascular disease is a heart disorder and the leading cause of death. Based on Riskesdas 2018, Indonesia's heart disease case is most widely found in the elderly population, with the highest prevalence at the age of 65-74 years old (4.6%). For those aged 75 and above, the prevalence of heart disease reaches 4.7%. This study aims to determine the relationship between smoking behavior and high-fat foods consumption with the incidence of heart disease among the elderly in Indonesia based on Riskesdas 2018 data analysis. This study is a quantitative research with a cross-sectional design and uses bivariate analysis with the chi-square test. The sample size for this study is 91.936. This study shows a relationship between smoking behavior (p = 0,000), high-fat food consumption (p = 0,000), and nutritional status with heart disease among the elderly (p = 0,000). Meanwhile, there is no relationship between age and gender with the incidence of heart disease among the elderly with p-values of 0,167 and 0,585 (p > 0,05). This study concludes that there is a relationship between smoking behavior and consumption of high-fat foods with the incidence of heart disease among the elderly in Indonesia.